forked from TheAlgorithms/Python
-
Notifications
You must be signed in to change notification settings - Fork 0
Commit
This commit does not belong to any branch on this repository, and may belong to a fork outside of the repository.
Binary Exponentiation for Multiplication
- Loading branch information
1 parent
f4c6578
commit f5917f5
Showing
1 changed file
with
50 additions
and
0 deletions.
There are no files selected for viewing
This file contains bidirectional Unicode text that may be interpreted or compiled differently than what appears below. To review, open the file in an editor that reveals hidden Unicode characters.
Learn more about bidirectional Unicode characters
Original file line number | Diff line number | Diff line change |
---|---|---|
@@ -0,0 +1,50 @@ | ||
""" | ||
* Binary Exponentiation with Multiplication | ||
* This is a method to find a*b in a time complexity of O(log b) | ||
* This is one of the most commonly used methods of finding result of multiplication. | ||
* Also useful in cases where solution to (a*b)%c is required, | ||
* where a,b,c can be numbers over the computers calculation limits. | ||
* Done using iteration, can also be done using recursion | ||
* @author chinmoy159 | ||
* @version 1.0 dated 10/08/2017 | ||
""" | ||
|
||
|
||
def b_expo(a, b): | ||
res = 0 | ||
while b > 0: | ||
if b&1: | ||
res += a | ||
|
||
a += a | ||
b >>= 1 | ||
|
||
return res | ||
|
||
|
||
def b_expo_mod(a, b, c): | ||
res = 0 | ||
while b > 0: | ||
if b&1: | ||
res = ((res%c) + (a%c)) % c | ||
|
||
a += a | ||
b >>= 1 | ||
|
||
return res | ||
|
||
|
||
""" | ||
* Wondering how this method works ! | ||
* It's pretty simple. | ||
* Let's say you need to calculate a ^ b | ||
* RULE 1 : a * b = (a+a) * (b/2) ---- example : 4 * 4 = (4+4) * (4/2) = 8 * 2 | ||
* RULE 2 : IF b is ODD, then ---- a * b = a + (a * (b - 1)) :: where (b - 1) is even. | ||
* Once b is even, repeat the process to get a * b | ||
* Repeat the process till b = 1 OR b = 0, because a*1 = a AND a*0 = 0 | ||
* | ||
* As far as the modulo is concerned, | ||
* the fact : (a+b) % c = ((a%c) + (b%c)) % c | ||
* Now apply RULE 1 OR 2, whichever is required. | ||
""" |